Phase II trial of vaccination with autologous, irradiated melanoma cells engineered by adenoviral mediated gene transfer to secrete granulocyte-macrophage colony stimulating factor in patients with stage III and IV melanoma - Sussman, Tamara A.; Severgnini, Mariano; Giobbie-Hurder, Anita; Friedlander, Philip; Swanson, Scott J.; Jaklitsch, Michael; Clancy, Thomas; Goguen, Laura A.; Lautz, David; Swanson, Richard; Daley, Heather; Ritz, Jerome; et al. (Frontiers in Oncology, 2024)
Background In the era of immune checkpoint blockade, the role of cancer vaccines in immune priming has provided additional potential for therapeutic improvements. Prior studies have demonstrated delayed type hypersensitivity and anti-tumor immunity with vaccines engineered to secrete granulocyte-macrophage colony-stimulating factor (GM-CSF). The safety, efficacy and anti-tumor immunity of GM-CSF secreting vaccine in patients with previously treated stage III or IV melanoma needs further investigation. Methods In this phase II trial, excised lymph node metastases were processed to single cells, transduced with an adenoviral vector encoding GM-CSF, irradiated, and cryopreserved. Individual vaccines were composed of 1x106, 4x106, or 1x107 tumor cells, and were injected intradermally and subcutaneously at weekly and biweekly intervals. The primary endpoints were feasibility of producing vaccine in stage III patients and determining the proportion of patients alive at two years in stage IV patients. Results GM-CSF vaccine was successfully developed and administered in all 61 patients. Toxicities were restricted to grade 1-2 local skin reactions. The median OS for stage III patients (n = 20) was 71.1 (95% CI, 43.7 to NR) months and 14.9 (95%CI, 12.1 to 39.7) months for stage IV patients. The median PFS in stage III patients was 50.7 (95%CI, 36.3 to NR) months and 4.1 (95% CI, 3.0-6.3) months in stage IV patients. In the overall population, the disease control rate was 39.3% (95%CI, 27.1 to 52.7%). In stage III patients, higher pre-treatment plasma cytokine levels of MMP-1, TRAIL, CXCL-11, CXCL-13 were associated with improved PFS (p<0.05 for all). An increase in post-vaccination levels of IL-15 and TRAIL for stage III patients was associated with improved PFS (p=0.03 for both). Similarly, an increase in post-vaccination IL-16 level for stage IV patients was associated with improved PFS (p=0.02) and clinical benefit. Conclusions Vaccination with autologous melanoma cells secreting GM-CSF augments antitumor immunity in stage III and IV patients with melanoma, is safe, and demonstrates disease control. Luminex data suggests that changes in inflammatory cytokines and immune cell infiltration promote tumor antigen presentation and subsequent tumor cell destruction. Additional investigation to administer this vaccine in combination with immune checkpoint inhibitors is needed.